Additional Evidence of Heteroscedasticity in the Market Model - Bey, Roger P.; Pinches, George E. (Journal of Financial and Quantitative Analysis, 1980)
Sharpe's market model [29] is widely used both by academic researchers and practitioners in finance, but it cannot be accepted with complete confidence until some of its basic assumptions are tested more thoroughly. The applicability, usefulness, and reliability of the model are functions of its conformity to real data, which in turn depends partly on the unresolved question of heteroscedasticity.